2018
DOI: 10.1021/acs.energyfuels.7b02973
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Ordered Spectroscopy Nuclear Magnetic Resonance as an Alternative Technique to Improve Asphaltene Characterization

Abstract: An asphaltene sample from a light Arabian crude oil was characterized using several analytical techniques, such as thermogravimetric analysis, nuclear magnetic resonance, Fourier transform infrared spectroscopy, and elemental analysis. The results showed that the sample has a high sulfur content and highly condensed aromatic compounds and the average molecular structure is predominantly of continental/island type; however, the presence of a significant amount of methylene carbons in long alkyl chains is clear.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…However, DOSY results indicates the presence of nanosized aggregates and some remaining solvent molecules (co-removal throughout the asphaltene separation stage applying ASTM D6560-12 process of sonication), and some long alkyl chain species clearly not chemically bonded to the aromatic centers, and the coexistence of archipelago and continental structural patterns. The chemical structure of the asphaltenes analyzed by Junior et al shows only nanosized aggregates at 8 wt % concentration significantly differ from most of the asphaltenes that exhibit micro and macroaggregates even at 3 wt %. , …”
Section: Application Of Nmr Spectrocopy On Asphaltenesmentioning
confidence: 89%
See 2 more Smart Citations
“…However, DOSY results indicates the presence of nanosized aggregates and some remaining solvent molecules (co-removal throughout the asphaltene separation stage applying ASTM D6560-12 process of sonication), and some long alkyl chain species clearly not chemically bonded to the aromatic centers, and the coexistence of archipelago and continental structural patterns. The chemical structure of the asphaltenes analyzed by Junior et al shows only nanosized aggregates at 8 wt % concentration significantly differ from most of the asphaltenes that exhibit micro and macroaggregates even at 3 wt %. , …”
Section: Application Of Nmr Spectrocopy On Asphaltenesmentioning
confidence: 89%
“…A Brazilian group has applied also 1 H DOSY NMR for studying an asphaltene probe derived from a Light Arabian crude oil . The major goals in conducting 1 H DOSY NMR are to determine the existence of asphaltene aggregates, to estimate the dimension of the aggregates, and to discuss the occurrence of maltenes occluded particles and entrained remaining solvent.…”
Section: Application Of Nmr Spectrocopy On Asphaltenesmentioning
confidence: 99%
See 1 more Smart Citation
“…NMR has proven to be a powerful tool in the determination of asphaltene structures, as shown in the recent review by Ok and Mal . Solution- and solid-state NMR have been used to study asphaltene structure. Fergoug and Bouhadda studied structural parameters of the asphaltenes derived from the Algerian Hassi Messoud oilfield using 1 H and 13 C liquid NMR, finding that the PAH region contains seven fused aromatic rings (7FAR). Scotti et al concluded, from a liquid-state 1 H and 13 C NMR study, that the most probable number of fused aromatic rings in asphaltene PAHs is seven.…”
Section: Introductionmentioning
confidence: 99%
“…[39] Subsequently, a number of research groups used DOSY NMR spectroscopy to investigate the structure, average size and self-association of the asphaltene aggregates. [1,[24][25][26]29,[43][44][45][46][47][48] A group of authors applied 1 H, 13 C and 1 H DOSY NMR experiments to study the relationship between the structural type (continental or archipelago) and aggregation properties of three different asphaltenes. The obtained results pointed towards the presence of predominantly continental structural type and confirmed the formation of nano-, micro-and macroaggregates, according to different diffusion coefficients.…”
Section: Diffusion-ordered Nmr Spectroscopy (Dosy)mentioning
confidence: 99%